A la gauche du Christ? Le 68 des catholiques chiliens - Elodie Giraudier (L'Ordinaire des Amériques)
In Chile, the social upheaval, the reforms and the political conflicts of the 1960s took place in institutions (like universities or political parties) and social circles close to the Catholic Church. The Christian Democracy that had been in charge since 1964 transitioned from a reformist phase towards a more conservative one as the Chilean political scene got more polarized. Some Chilean Catholics were attracted by Marxism, some maintained their centrist positions and others reaffirmed their inflexible positions. Tensions were also to be found elsewhere : after the occupation of the Catholic University of Santiago de Chile (August 11th 1967), a new wave of student strikes started in April 1968. The Church was also affected by this new context : in 1968, the Latin American Episcopal Conference from Medellin suggested members of the clergy adopt a lifestyle more in tune with that of their flock—this was « the preferential option for the poor ». In the long run, this period brought about new expectations but also reactionary attitudes (which led to the military coup d’Etat and the dictatorship), whose memory is still ambivalent today.